Substantiation of technology for producing of biologically active supplement from see cucumber (Apostichopus japonicus) - Anna I. Chepkasova; Tatiana N. Slutskaya; Yury N. Kuznetsov (Известия ТИНРО, 2017)
Sea cucumber Apostichopus japonicas is distinguished by high diversity of biologically active substances. Their extraction by honey is one of traditional ways of the sea cucumber using as a therapeutic and prophylactic agent. Mixture of xanthan gum and locust bean gum with apple pectin in different concentrations is used as the honey solvent. Organoleptic properties and viscosity of the compound of sea cucumber mixed with this honey solvent in different proportions are evaluated and their ratio providing uniform and stable consistency with viscosity 3.0-4.5 Pa.s during long-term storage is chosen as the optimal one. The product heating to 70оC causes a significant increase in viscosity that can be explained by loss of water from muscular tissue of the sea cucumber and its binding with the structure-forming agent. The heating of the compound with 1 % of xanthan gum causes the viscosity increasing in 4 times as compared with the control sample. The sequence of technological methods for producing the biologically active supplement «Trepang on honey» with stable structure and composition is proposed. The supplement contains 0.3 % of glucosamine and 0.1 % of glycosides. Daily dosage of this supplement is determined.